Legitimação democrática do Supremo Tribunal Federal e a necessidade de um Tribunal Constitucional brasileiro exclusivo - Saraiva Filho, José Leite (2025)
There has been a growing social, political, and academic interest in the democratic legitimacy of courts responsible for the effectiveness of Constitutions, through abstract and concentrated constitutional control of norms and certain administrative acts, especially in the contemporary hyperconnected society. In this context, this study aims to emphasize that its origin comes from the overlap of judicial functions with those of a Constitutional Court and claims that it is detrimental to legitimizing the Supreme Federal Court as the ultimate official interpreter of the Constitution. This cumulation is influenced by the maintenance of the state structure and access to power, like previous republican Constitutions, since the National Constituent Assembly was congressional rather than exclusive. Furthermore, this investigation seeks to demonstrate the intrinsic connection between the interpreter's circumstances in the process of norm interpretation-concretization and the exogenous and endogenous aspects that led them to the position of official constitutional exegete, as well as the institutional framework in which they undertake their respective activity, as these are relevant to the democratic legitimation of the interpretation result. It is then suggested that the need to separate the constitutional court activity from the executive power, creating a specific state body, dissociated from any of the constituted powers. This would ensure the adequacy of the majority constitutional framework for concentrated and abstract constitutionality control. It would include the institution of a mandate for its members with specific and exclusive appointment, originating from the three Powers, like in many countries that adopt this type of constitutionality control